DEVELOPING A CHARACTER-BASED ENGLISH LANGUAGE TEXTBOOK FOR GRADE VII OF JUNIOR HIGH SCHOOL BASED ON THE CURRICULUM 2013 - ., Luh Tiwika Praba; ., Drs.Gede Batan,MA; ., Ni LP. Eka Sulistia Dewi, S.Pd. M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
This study aimed at developing a character-based English textbook for grade VII of junior high school based on the curriculum 2013. The product of this study was developed based on modified instructional design proposed by Dick, Carey, & Carey (2001). The instructional design consists of identifying instructional goal, conducting instructional analysis, analyzing learners and context, writing performance objectives and indicators, developing judgment instrument, developing design of the textbook, developing content of the textbook, conducting formative evaluation, revising the textbook, limited field trial, and the final product. The subjects of this study were 29 students of class VII.A7 of SMP Negeri 1 Singaraja. There were two experts involved in evaluating the textbook, i.e. a lecturer who expert in material development and an English teacher. From the experts judgment, it is obtained the value of Cronbach’s Alpha coefficient is 0.938 (excellent). In addition, the total mean score of experts’ judgment is 4.35, which is categorized as excellent. The result shows that the character values of the textbook presented in the content and presentation of the textbook. It term of presentation, the textbook followed the steps of scientific approach, namely observing, questioning, exploring, associating, and communicating. Further, from the limited field trial, 24.1% students give rating 4 (happy) toward the textbook implementation and 75.9% give rating 5 (very happy). It means that all students give positive response upon the textbook. Thus, the textbook which developed in this research is feasible to be used for grade VII based on the curriculum 2013.keyword : English textbook, curriculum, curriculum 2013, character-based instruction